GLOBAL HOSPITALIZATION TRENDS FOR CROHN'S DISEASE AND ULCERATIVE COLITIS: SYSTEMATIC REVIEW WITH TEMPORAL ANALYSES. (22nd January 2022) - Buie, Michael; Quan, Joshua; Windsor, Joseph; Coward, Stephanie; Gearry, Richard; Hansen, Tawnya; King, James; Kotze, Paulo; Ng, Siew; Mak, Joyce; Panaccione, Remo; Seow, Cynthia; et al.
Abstract: INTRODUCTION: The evolving epidemiologic patterns of IBD throughout the world, in conjunction with advances in therapeutic treatments, may influence hospitalization rates of IBD in the 21 st century. We performed a systematic review with temporal analysis of hospitalization rates for IBD across the world in the 21 st century. METHODS: We systematically reviewed MedLine and Embase for population-based studies reporting hospitalization rates for IBD, Crohn's disease (CD), or ulcerative colitis (UC) since 2000. Log-linear models were used to calculate average annual percentage change (AAPC) with associated 95% confidence intervals (CI). Random effects meta-analysis pooled AAPCs stratified by countries in the Western world (i.e. North America, Western Europe, and Oceania) versus newly industrialized countries in Eastern Europe, Asia, Latin America, and Africa. Secondarily, we compared hospitalization rates by primary diagnosis of IBD versus all-cause hospitalizations. QGIS 3.44 was used to create a choropleth map of AAPC and ArcGIS Pro 2.4.1 was used to develop an online, interactive map of global hospitalization trends. RESULTS: Data were extracted from 87 studies comprising 42 countries. Overall, hospitalization rates were stable in countries of the Western world for IBD (AAPC=−0.25; 95% CI: −0.90, 0.41, n =22), CD (AAPC=2.76; 95% CI: −0.62, 6.15, n =8), and UC (AAPC=1.44; 95% CI: −1.98, 4.86, n =7) (Table 1). However, heterogeneity between countries was observed, for example, hospitalization rates for CD (−0.02%; 95%CI: −0.52, 0.48) and UC (0.40%; 95%CI: −0.81, 1.63) were stable in the USA, but increasing for CD (2.05%; 95%CI: 1.25, 2.84) and UC (1.69%; 95%CI: 0.99, 2.39) in Portugal (Figure 1). CD and UC hospitalization rates in newly industrialized countries increased in Mexico (CD: 5.21%; 95%CI: 3.07, 7.39; UC: 5.96%; 95%CI: 4.30, 7.64), Chile (CD: 6.03%; 95%CI: 5.21, 6.86; UC: 3.78%; 95%CI: 3.43, 4.13), Bahrain (CD: 12.98%; 95%CI: 7.83, 18.38; UC: 7.27%; 95%CI: 2.12, 12.69), and Hong Kong (CD: 8.67%; 95%CI: 5.81, 11.61; UC: 0.14%; 95%CI: −2.21, 2.53), but significantly decreased in Brazil for CD (−3.22%; 95%CI: −5.24, −1.15) and UC (−3.41; 95%CI: −4.63, −2.18) (Figure 1). Studies that defined hospitalization rates as the primary diagnosis of IBD versus all-cause hospitalizations may explain heterogeneity between countries (Table 1). CONCLUSION: Hospitalization rates for IBD are stabilizing in North America, Europe, and Oceania. In contrast, newly industrialized countries in Asia and Latin America have rapidly rising hospitalization rates, contributing to an increasing burden on global healthcare systems. Future studies should explore clinical and methodological factors that explain heterogeneity between country-specific hospitalization rates.